Improving the Mechanisms of Financing Higher Education Institutions with Foreign Capital - Bozorov Alisher Rozimurodovich (Scientific Trends, 2025)
This article discusses the role, advantages and existing problems of financing with foreign capital in the modernization of the higher education system of Uzbekistan. Based on world experience, mechanisms for attracting foreign investment are analyzed. Also, recommendations are developed to expand the use of foreign financial resources in the higher education system of Uzbekistan. The article is written on the basis of scientific research methods and is based on statistical data, legislative documents and international experience.
Keywords: Higher education, foreign investment, financing mechanism, public-private partnership, grant, loan, academic cooperation.